Table of Content - - (Journal of natural sciences, life and applied sciences, 2025)
Table of Content:1. Analysis of Morphometric Characteristics and Land Use in the Oued Tamri and Adoudou Watersheds, Morocco: A Spatial and Temporal Study Using GIS and Remote SensingDr. Soukaina Amrani2. Modeling Topographic Variables in Relation to Land Cover and Land Use Changes in Hail CityLecturer \ Afaf Salem Al-Shammari ,Dr. Abdul-Rahman Suleiman Al-Nisayan3. Maxwell's Equations Under Lorentz Transformations: Investigating the Spontaneous Emergence of Magnetic Charge and Current DensitiesMr. Louai Hassan Elzein Bashier
Keywords: Journal of Natural Sciences, Life and Applied Sciences